Online learning for WHO priority diseases with pandemic potential: evidence from existing courses and preparing for Disease X - Heini Utunen; Anna Tokar; Mafalda Dancante; Corentin Piroux (BMC, 2023)
Abstract Background OpenWHO is the open-access learning platform of the World Health Organization (WHO) that provides online learning for health emergencies with essential health knowledge for emergencies. There is emphasis for courses on severe emerging diseases with epidemic and pandemic potential to help frontline health workers prevent, control and respond to infectious diseases. This research addresses the question of how the existing OpenWHO online courses on infectious disease were used in the countries of disease occurrence and how to prepare for disease X, a novel or unknown pathogen with pandemic potential. Methods OpenWHO collects self-declared demographic data from learners among which there is data on geographical location of learners. Data in infectious disease courses use on OpenWHO was collected and examined and additionally information languages used in the outbreak locations was collected. Results For most diseases in focus the online learning materials were used in countries with burden of disease. This suggests the learning material production needs to be targeted for outbreak and epidemic events. Conclusions Findings inform the use of learning materials in disease outbreaks. Further, this use case data confirms learning providers need to add offerings in languages spoken in outbreak impacted areas.